2010
DOI: 10.1063/1.3488815
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent simulation of intermediate band solar cells: Effect of occupation rates on device characteristics

Abstract: In order to design optimum structures for intermediate band solar cells, simulations based on self-consistent drift-diffusion model with a suitable treatment of the intermediate band in device domain are necessary. In this work, we have included the dependence of occupation rate of intermediate band at each position on optical generation rate via the intermediate band. Typical material parameters of GaAs were used except for the absorption coefficient of each corresponding band-to-band transition. Simulation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 17 publications
4
37
0
1
Order By: Relevance
“…However, it becomes possible to sustain a reasonable population of photo-generated electrons even in a non-doped QD-IB solar cell if it was operated under concentrated sunlight, typically 100 ∼ 1000 suns. Yoshida et al [19] has also recently reported similar results based on a self-consistent device simulation. The sub-bandgap photons can optically pump the electrons both from VB to IB states and from IB to CB states.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, it becomes possible to sustain a reasonable population of photo-generated electrons even in a non-doped QD-IB solar cell if it was operated under concentrated sunlight, typically 100 ∼ 1000 suns. Yoshida et al [19] has also recently reported similar results based on a self-consistent device simulation. The sub-bandgap photons can optically pump the electrons both from VB to IB states and from IB to CB states.…”
Section: Introductionsupporting
confidence: 68%
“…The details can be found elsewhere [19,22]. In particular, the effects of doping in the IB region and incident sunlight concentration on the cell characteristics were investigated.…”
Section: Efficiency Analysis Of Qd-ib Solar Cellmentioning
confidence: 99%
“…It would, however, become possible to sustain a reasonable population of photogenerated electrons even in a nondoped QD-IBSC under concentrated sunlight, typically 100 to 1000 suns. Yoshida et al 21,22 also reported similar calculated results based on a self-consistent device simulation method. Although the theoretical analysis of IBSCs commonly adopts a detailed balanced model, 2 Sullivan et al 23 have recently shown that the optical and nonradiative electrical trapping cross sections of impurities in the IB region determine the performance of IBSCs in the case of the nonradiative recombination lifetimes dominating over radiative lifetimes.…”
Section: Introductionsupporting
confidence: 61%
“…A self-consistent drift-diffusion simulation 21,22 was performed to clarify the effect of doping in the QD-IB region and the effect of sunlight concentration on the SC characteristics. Here, the optical generation (G ij ) and recombination (R ij ) rates between VB-IB and IB-CB are assumed to be locally balanced, i.e., E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 1 4 0…”
Section: Simulated Performance Of Intermediate Band Solar Cells With mentioning
confidence: 99%
“…13 Furthermore, it has been reported that the short-circuit current of a real IBSC is strongly dependent on the occupation of the IB, since the number of intermediate states is limited. 14 In order for photo-generation to occur, the lower state must be occupied by an electron and the upper state must be empty, and the strength of this transition is described by absorption coefficient of photons at the energy. 15 In a real IBSC, the absorption coefficient for IB-CB transition depends linearly on the occupation factor of the intermediate states f IB , as a IC f IB , where a IC is the absorption coefficient constant for the transition, so a small occupation of the IB leads to a small contribution to the short-circuit current from the IB.…”
mentioning
confidence: 99%